2006
DOI: 10.12968/ijtr.2006.13.9.21784
|View full text |Cite
|
Sign up to set email alerts
|

Potential screening measures for depression and anxiety after stroke

Abstract: Depression and anxiety are common problems after stroke. The National Clinical Guidelines for stroke (Royal College Physicians, 2004) recommend that all patients are screened for low mood. The aim of the review was to identify measures which could be used for this purpose and to review the evidence for their sensitivity and specificity with stroke patients. A literature search was conducted using electronic databases, including Medline, Embase, PsycInfo and CINAHL, to identify articles published in peer revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…However, the DT demonstrated the lowest AUC of all measures. It did not demonstrate a sensitivity-specificity combination that met with guidelines for a good depression screening tool 21 and had the weakest correlations with the other scales. Although factor analysis of the K-10 has identified a depression specific factor, 35 the DT addresses global distress in a single item, potentially capturing a range of nondepressive states of emotional distress (reducing sensitivity).…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…However, the DT demonstrated the lowest AUC of all measures. It did not demonstrate a sensitivity-specificity combination that met with guidelines for a good depression screening tool 21 and had the weakest correlations with the other scales. Although factor analysis of the K-10 has identified a depression specific factor, 35 the DT addresses global distress in a single item, potentially capturing a range of nondepressive states of emotional distress (reducing sensitivity).…”
Section: Discussionmentioning
confidence: 81%
“…16 -20 Several other depression measures commonly used in stroke practice (eg, Geriatric Depression Scale) also have evidence supporting their use. 21 Evidence for diagnostic accuracy of the BDI-II, DT, and K-10 is lacking in stroke populations. Diagnostic accuracy of the original BDI has been evaluated, 18,[22][23][24] BDI-II, 12 although a factor analytic study in a neurorehabilitation population indicated the measure provides a meaningful severity score of depression in patients with stroke.…”
Section: Results-internalmentioning
confidence: 99%
See 3 more Smart Citations